Accuracy of Neutrophil/Lymphocyte Ratio as Predictor of Neoadjuvant Chemotherapy Response in Locally Advanced Breast Cancer at Dr. Mohammad Hoesin General Hospital Palembang - M. Aprizal Putera; Mulawan Umar; Erial Bahar (Sriwijaya Journal of Surgery, 2021)
Introduction: Breast cancer is one of the most common neoplasm occurs in women. Neoadjuvant Chemotherapy (NACT) is widely used in Locally Advanced Breast Cancer (LABC) and Inflammatory Breast Cancer (IBC), to reduce tumor size (down-sizing), and further allowing breast-conserving surgery to be performed. Accurate markers are needed to prevent impractical chemotherapy that allows patients to receive definitive surgery in a timely manner. Previous study showed neutrophil/lymphocyte ratio (NLR) was superior in predicting long-term outcomes over PLR. This study aims to evaluate the relationship between the NLR value and neoadjuvant chemotherapy response in patients with locally advanced breast cancer at Dr. Mohammad Hoesin General Hospital Palembang. Methods: This study is a prognostic test of the NLR accuracy to predict the response of neoadjuvant chemotherapy in patients with locally advanced breast cancer. The study included 113 patients as study subjects. Results: The obtained NLR cut off point value was â‰¤ 2.92 with an area under the ROC curve (AUC) of 92.2%. The diagnostic measures of the NLR prognostic test had sensitivity of 93%, specificity of 93%, Positive Predictive Value of 97%, Negative Predictive Value of 82%, and accuracy of 93%. There is a significant relationship between NLR and chemotherapy response in patients with locally advanced breast cancer (p = 0.000). Conclusion: There is a significant relationship between NLTR and chemotherapy response. NLR can be used as a predictor of neoadjuvant chemotherapy response with a good degree of accuracy.